Organizing U.S. foreign aid : confronting the challenges of the twenty-first century - Lancaster, Carol; Van Dusen, Ann. (Washington, D.C. : Brookings Institution Press, 2005)
"Recommends fundamental reorganization of U.S. foreign aid, currently based on outsourcing and management for results, in favor of a more unified approach emphasizing development education, stringent evaluation, and a new approach to contracting"--Provided by publisher
A new urgency: international development and U.S. foreign policy -- The nature of development -- What is foreign aid? -- The mission and purposes of U.S. foreign aid -- A short history of aid -- Organizational landscape of U.S. foreign aid -- Structure and processes of the U.S. Agency for International Development -- The political context of U.S. international assistance -- Alternative approaches: other aid-giving donor countries -- Foreign aid in the twenty-first century -- Challenges and opportunities: recommendations and options for organizing U.S. foreign aid.
Includes bibliographical references (pages 67-71) and index.).
Print version record.
English.
JSTOR
Keywords: Economic assistance, American; Aide économique américaine.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Economic assistance, American